2019
DOI: 10.1016/j.molcel.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Control eIF5A Hypusination, TFEB Translation, and Autophagy to Reverse B Cell Senescence

Abstract: Graphical Abstract Highlights d The endogenous polyamine spermidine maintains autophagy via hypusinating eIF5A d Hypusinated translation factor eIF5A controls TFEB expression and autophagy d Spermidine restores B cell responses in old mice and humans d TFEB levels decline with age and can be used as drug target/ biomarker for human aging SUMMARYFailure to make adaptive immune responses is a hallmark of aging. Reduced B cell function leads to poor vaccination efficacy and a high prevalence of infections in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
229
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(234 citation statements)
references
References 61 publications
4
229
0
1
Order By: Relevance
“…EIF5A also regulates mitochondrial respiration via initiation from alternative start codons. In addition, EIF5A restricts RNA virus infections [22, 55, 64, 78, 101, 110, 112, 113, 125, 148, 152, 164, 235]. It is important to note in this context that ATXN2 is cleaved by Coxsackie-virus and Polio-virus, during their optimized efforts to diminish host cell defenses against invading viral RNA [84].…”
Section: Resultsmentioning
confidence: 99%
“…EIF5A also regulates mitochondrial respiration via initiation from alternative start codons. In addition, EIF5A restricts RNA virus infections [22, 55, 64, 78, 101, 110, 112, 113, 125, 148, 152, 164, 235]. It is important to note in this context that ATXN2 is cleaved by Coxsackie-virus and Polio-virus, during their optimized efforts to diminish host cell defenses against invading viral RNA [84].…”
Section: Resultsmentioning
confidence: 99%
“…Spermidine is an important polyamine capable of inducing autophagy ( 21 ) and responsible for hypusination of the eukaryotic translation initiation factor eIF5A ( 22 ). eIF5A activates the autophagy transcription factor TFEB and regulates proteins responsible for mitochondrial respiration ( 23 ).…”
Section: Fig1mentioning
confidence: 99%
“…We have recently shown that treating old but not young mice with the metabolite spermidine improves autophagy levels in B lymphocytes due to an age-related decline of endogenous spermidine 15 . Here we sought to confirm this in human lymphocytes.…”
Section: Figure S4mentioning
confidence: 99%
“…Several downstream mechanisms of spermidine-induced autophagy have been described in mice, including the inhibition of histone deacetylases 14 . Recently we uncovered a novel pathway in which spermidine lends a residue for the hypusination of the translation factor eIF5a, which is necessary for the translation of a three proline motif present in the master transcription factor of autophagy and lysosomal biogenesis, called TFEB 15 . We demonstrated this pathway operates in activated B cells, which upon activation have an unusually high protein synthesis rate, owing to the high production of immunoglobulins.…”
Section: Introductionmentioning
confidence: 99%